A Tale of Two Travellers in King Alfred’s Court - Miguel Alarcão (Medievalista)
Considering just the English medieval case, it seems reasonable to assume that some sorts or forms of travel writing, literary or otherwise, must have existed before such canonical texts as The Travels of Sir John Mandeville, the anonymous The Land of Cockaygne or Geoffrey Chaucer’s The Canterbury Tales (14th century). Indeed, the two short accounts I will present were added to, and included in, the Old English translation of Paulus Orosius’s Historiarum (or Historiae) adversum Paganos Libro Septem (5th century), ordered by, and made for, Alfred the Great, King of Wessex (871-899)